RELEVANSI KEBIJAKAN TPPA 2011 TERHADAP NEGARA-NEGARA ANGGOTA WTO DALAM PERDAGANGAN INTERNASIONAL - Sidiqah, Meliyani (LITIGASI, 2022)
Tobacco Plain Packaging Act (TPPA) 2011 is one of the laws enacted by Australia which is opposed by tobacco producing countries because it requires plain packaging of cigarettes and other tobacco products. The purpose of this research are to find out the relevance of the TPPA 2011 promulgated by Australia to the trade provisions in the WTO, and to find out the legal consequences for WTO members that have bilateral relation with Australia. The specifications of this research is descriptive. The type of research is normative juridicial research. The approach method is statute approach, and case aprroach. The data collection technique is through the study of primary, secondary and tertiary legal material which are analyzed using qualitative methods. The first result is, TPPA 2011 is not relevant to the trade provisions in the WTO. The second result is the WTO members that have bilateral relation with Australia must be willing to comply with the TPPA 2011. Keywords: Australia; cigarette plain packaging;TPPA 2011.